Temporal peripapillary vitreoretinal traction associated with bergmeister’s papilla: A rare case report and brief review - Tung, Hoang Thanh; Subramanian, Prem S.; Tung, Le Anh (Tạp chí Nghiên cứu Y học, 2026)
Bergmeister’s papilla is a rare congenital optic disc remnant that is usually benign. We report a case of temporal peripapillary retinal traction associated with Bergmeister’s papilla in a 42-year-old asymptomatic woman. She presented with mild near-vision blur due to presbyopia, but normal distance vision and had 20/20 visual acuity bilaterally. Anterior segment and intraocular pressures were normal. Fundus examination revealed a large Bergmeister’s papilla in the right eye, and spectral-domain optical coherence tomography (SD-OCT) demonstrated temporal peripapillary traction with focal cystic change while preserving the foveal contour. The patient was counseled and scheduled for six-month follow-up. This case highlights that although Bergmeister’s papilla is typically benign, it may occasionally induce subtle tractional changes, and comprehensive evaluation using OCT is essential for accurate diagnosis and long-term monitoring.